MODEL ALAT PELONTAR BOLA FUTSAL (ZPD 02) UNTUK KETERAMPILAN TEKNIK PERMAINAN FUTSAL - Zusyah Porja Daryanto; Muhammad Suhairi; Ilham Surya Fallo; Hasan Hasan; Rusdaniyar Rusdaniyar (Jurnal Pendidikan Olah Raga, 2022)
The purpose of this study was to develop a futsal ball thrower for skill training in futsal game. The development was conducted in order to advance the previous machine which already existed to be more maximum in helping the athlete for exercising futsal skills. The developed machine was equipped with: 1) A basket which can storage 5 balls; 2) The various speed of ejection; 3) Two ejection heads which the angle can be set up; 4) Manual and automatic operation; 5) Flexibility that the machine can be move in every direction (left, right, center, upper, and lower). Those features can be used to train some futsal skills in shooting, heading, controlling, passing, volley kick, and reaction training for goal keeper. The study used Research and Development of Borg and Gall with 10 stages such as: 1) Research and information gathering; 2) Planning; 3) Early form of product development; 4) Field pretest; 5) Main product revision; 6) Main field test; 7) Product operational revision; 8) Operational field test; 9) Final revision of the product; and 10) The dissemination and implementation of the product result of the ball throwing machine model (ZPD 02) for futsal skill training.